The Consequences of the decay totalitarian state and migration of the population in condition of market economies (Journal of actual problems of jurisprudence, 2019)
In given article are considered problems to evolutions to migration of the population after decay USSR. It IsAnalyzed factors, influencing upon moving the people, problems populations from Kyrgyzstana, questionsentry and exit in own country.Keywords: state, migration, population, market economy.